PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN UTANG, DAN KEPUTUSAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI PEMODERASI - Nurdiansyah, Wegig; Endang Etty Merawati; Syamsul Bahri (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2024)
Since Covid-19 till now, the volatility of the IHSG has become increasingly uncertain. Current market uncertainty raises concerns about reducing investor participation. However, in the 2020-2022, there was a big increase in the number of investors reaching 300%, the highest in history. Ferris (1997) stated that the value of a company is reflected in its stock price. However, the current index volatility does not show this. The role of financial managers is very important in maintaining the value of the company. There are three functions of financial management, namely investment decisions, debt, and dividends. (Hanafi, 2008). This study aims to analyze investment decisions, debt decisions, and dividend decisions on firm value and uses profitability as a moderator with a case study of property and real estate companies listed on the Indonesia Stock Exchange. The method used in this study is secondary data collection through the Indonesia Stock Exchange on property and real estate sector for the period 2018 - 2023. The results of this study indicate that investment decisions and debt decisions have no effect on firm value. While dividend decisions have a positive and significant effect. Simultaneously, the three variables also have a positive and significant effect on firm value. Then, profitability is not able to moderate investment decisions and debt decisions on firm value. However, it is proven to have a positive and significant effect in moderating dividend decisions on firm value in property and real estate sector.